2015
DOI: 10.1021/acs.biochem.5b00452
|View full text |Cite
|
Sign up to set email alerts
|

Domain Selection in Metallothionein 1A: Affinity-Controlled Mechanisms of Zinc Binding and Cadmium Exchange

Abstract: Mammalian metallothioneins (MTs) are small, metal binding proteins implicated in cellular metal ion homeostasis and heavy metal detoxification. Divalent, metal-saturated MTs form two distinct domains; the N-terminal β domain binds three metals using nine Cys residues, and the C-terminal α domain binds four metals with 11 Cys residues. Domain selection during zinc binding and cadmium exchange to human MT1A was examined using a series of competition reactions with mixtures of the isolated domain fragments. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 60 publications
(163 reference statements)
0
24
0
Order By: Relevance
“…Although some isoform-specific differences likely exist, MT-1a cooperatively forms cadmium clusters in the α-domain and this has been reported in both the full-length protein and the isolated α-domain fragment [67,89]. In competition experiments, a slight preference for α-domain metalation is observed that is exaggerated at lower pH [98]. Thus at least for the MT-1/2 isoforms cadmium metalation is α-domain specific, a phenomenon that becomes more apparent at lower pH.…”
Section: Covalent Modificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Although some isoform-specific differences likely exist, MT-1a cooperatively forms cadmium clusters in the α-domain and this has been reported in both the full-length protein and the isolated α-domain fragment [67,89]. In competition experiments, a slight preference for α-domain metalation is observed that is exaggerated at lower pH [98]. Thus at least for the MT-1/2 isoforms cadmium metalation is α-domain specific, a phenomenon that becomes more apparent at lower pH.…”
Section: Covalent Modificationmentioning
confidence: 99%
“…Domain specificity is a concept that has long been investigated in the case of metallothioneins with its two-domain structure consisting of a smaller, 9 cysteine β-domain and a larger 11-cysteine α-domain [94,95,96,97,98]. Domain specificity has been primarily investigated by NMR spectroscopy [95] and ESI-MS [98,99] due to the ability of both techniques to identify the domain in which the metal is bound.…”
Section: Covalent Modificationmentioning
confidence: 99%
See 3 more Smart Citations